Adverse effects associated with the use of N95 mask among health-care workers at the COVID-19 care units: A cross-sectional study in Sulaimani city, Iraq - Saad Abdulrahman Hussain; Naza Mohammed Ali Mahmood; Trefa Mohammed Ali Mahmood; Neega Aras Mohammed Salih; Zainab Saad Abdulrahman (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Health-care workers have to use the N95 mask as a part of the protection kit during the COVID-19 pandemic. The adverse effects of such practice are not fully elucidated. The study aims to evaluate negative impacts of N95 face masks on health-care personnel at COVID-19 care units. MATERIALS AND METHODS: One hundred and twenty-two health-care workers (aged 20-58 years) from various health-care settings in Sulaimani, Iraq, from January to August 2020, were enrolled in this prospective, cross-sectional study. The physiological variables (blood pressure, heart rate, and oxygen saturation) were recorded before putting on the N95 mask and postremoval of the mask. The incidence of adverse effects such as headache, difficulty breathing, redness, irritation, and dizziness were also reported as a number and percent at the end of the work shift. RESULTS: There was a statistically significant difference in the physiological parameters after removal of the mask compared with baseline. Only diastolic pressure was significantly lower in those working >6 h when compared to those working 1-6 h. The changes in physiological markers were poorly and nonsignificantly associated with the duration of wearing the mask. Moreover, 67.2%-70.5% of the participants complain of headaches and breathing difficulties, while 45.9%-51.6% reported signs of itching, redness, and irritation. However, health-care workers who put on the face mask >6 h showed signs of headache, breathing difficulties, and itching at the exposed areas higher than those working for 1-6 h. CONCLUSION: N95 mask negatively impacts the physiological variables of health-care providers. The adverse effects may lead to excessive exhaustion after long shifts in the intensive care unit during treatment of COVID-19 patients.